Designing a Vietnamese - Japanese translation course for the Japan studies - Tran, Thị Chung Toan (Vietnam National University, Hanoi, 2020)
This paper, based on the years of teaching the Japanese language and other courses ralated to japan studies, point out the importance and demands of setting-up a Vietnamese - Japanese translation course for the last memester in the fourth year students at the Japan studies, Faculty of Oriental studies. By that time, students have already completed the elementary and intermediate levels of Japanese and a number of specialization subjects, therefore, the course will contribute to the consolidation and strenthening knowledge and skill of using the language. It provides theoretical basis and translation skills for students'further self-study